Initial Gas Reserve Estimation For Wells W-1, W-1A, and W-2 Based on Well Log Data in the Wailawi Field, East Kalimantan - Reis, Julieta Da Silva Dos (Journal Research of Social Science, Economics, and Management, 2025)
The Wailawi Field, located in East Kalimantan, is a mature oil and gas field that still holds potential hydrocarbon reserves despite experiencing a decline in production. This study aims to evaluate the remaining hydrocarbon reserves in Well X based on well log data to assess the potential for field redevelopment. The methods used include qualitative and quantitative petrophysical analyses using gamma ray, resistivity, neutron, and density logs, which are then integrated with volumetric calculations to determine the Original Gas in Place (OGIP), Recoverable Reserves (Rtotal), and Remaining Reserves (RR). The petrophysical analysis results show that Well Wailawi-1 has an average porosity of 0.16 and a water saturation of 0.77; Well Wailawi-1A has a porosity of 0.16 and water saturation of 0.61; and Well Wailawi-2 has a porosity of 0.18 and water saturation of 0.64. High porosity and low water saturation values indicate good reservoir quality for hydrocarbon accumulation. Based on volumetric calculations, the OGIP values obtained are 92.06 BSCF for Well W-1, 15,552,989,133 MSCF for Well W-1A, and 58,545,637,822 MSCF for Well W-2. With a recovery factor of 85%, the total recoverable reserves (Rtotal) reach 78,250,771,653 MSCF, with cumulative production (Np) of 23,210,000,000 MSCF, resulting in remaining gas reserves (RR) of 55,040,771,653 MSCF. These results indicate that the Wailawi Field still possesses economically viable hydrocarbon reserves that can be developed through workover operations, infill drilling, and optimization of productive zones.